Resistance of pearlspot larvae, Etroplus suratensis, to redspotted grouper nervous necrosis virus by immersion challenge. Issue 2 (29th November 2018) - Marappan, Makesh; Rengarajan, Aathithya; Nallala, Venkata Satyanarayana; Sukumaran, Krishna; Bera, Aritra; Sivaramakrishnan, Thirugnamurty; Thiagarajan, Govindarajan; Kailasam, Muniyandi; Koyadan Kizhakedath, Vijayan
Abstract: Viral nervous necrosis (VNN) affects more than 120 species mostly belonging to the order Perciformes. However, none of the brackishwater species belonging to the family Cichlidae under the order Perciformes are reported to be susceptible. Hence, the present experiment was undertaken to study the susceptibility of the brackishwater cichlid, pearlspot, Etroplus suratensis to NNV. Thirty‐day‐old pearlspot larvae were infected with NNV by immersion. Mortality was recorded till 14 days post‐infection, and the infected larvae were subjected to nested RT‐PCR and histology. The virus was isolated from infected larvae using SSN‐1 cells. To study the replication of the virus in vitro, primary cultured brain cells of E. suratensis and IEK cells were infected with NNV. No mortality was observed in any of the control or experimentally infected larvae. However, the experimentally infected larvae were positive for NNV by nested RT‐PCR and the virus was isolated using SSN‐1 cells. Further, the infected pearlspot brain cells and IEK cells showed cytopathic effect at second and third passage of the virus and they were positive for NNV by nested RT‐PCR. Pearlspot is relatively resistant to VNN although the virus could replicate in the larvae and in cell culture.